UR_GERICHTE 2017_OG V 17 vom 13. Januar 2017 - UR Obergericht (2017)
1. Fürsorgerische Unterbringung. Art. 314b Abs. 1, Art. 426 Abs. 1 - 3, Art. 429 Abs. 3, 430 Abs. 2 Ziff. 1 - 4, Art. 430 Abs. 3 ZGB. Art. 34 Abs. 3 VRPV.